Microwave Activation of Electrochemical Processes in Ionic Liquid Impregnated Ionomer Spheres - Dale, S; Compton, R; Marken, F (2012)
The redox system K 4Fe(CN) 6 adsorbed into anion exchanger particles (Dowex 1×2 of typically 200μm diameter) and impregnated with 1-butyl-3-methyl-imidazolium tetrafluoroborate ionic liquid (BMIM +BF 4-) in contact to a 50μm diameter platinum microelectrode show well-defined Fe(III/II) voltammetric responses. Processes are studied at the ionic liquid sphere | electrode | gas interface in the presence of dry or 80% relative humidity argon gas flow. Due to the hygroscopic nature of BMIN +BF 4- currents are sensitive to humidity levels. Pulsed and continuous microwave activation (2.45GHz) is shown to occur locally at the tip of the platinum microelectrode due to focusing of microwave energy. Impedance experiments reveal the presence of a thin active film of ionic liquid. © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.